Áreas verdes de Limeira - SP - Silva, Paula Angélica da [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This paper is aimed to analyze the distribution of green areas in public spaces of the Limeira city. This study seeks to diagnose the current situation of the distribution of green areas in the city of Limeira and how these areas contribute to the quality of life of city residents. The concept of public green areas can be defined in different ways , and for this study were considered spaces where there is a prevalence of vegetation, parks , public gardens , squares and medians of avenues performing aesthetic and ecological , whose soil is not completely covered . The presence of urban green areas has several functions, such as a space for recreation , environmental education and interpretation , and thus contribute to a greater closeness between man and nature . The aim of this study is to discuss what benefits, incentives and difficulties exist for the maintenance and expansion of green areas in the city and investigate the population's perception of, and their relationship with, these spaces

Este trabalho tem como objetivo principal analisar a distribuição de áreas verdes nos espaços públicos da cidade de Limeira. Este estudo busca diagnosticar a atual situação da distribuição de áreas verdes na cidade de Limeira e de que forma estes espaços verdes contribuem a qualidade de vida dos habitantes da cidade. O conceito de áreas verdes públicas é definido de diferentes formas, e para este estudo, foram considerados os espaços livres onde há predomínio de vegetação, parques, jardins públicos, praças e canteiros centrais de avenidas que exercem função estética e ecológica, cujo solo não é totalmente impermeabilizado. A presença de áreas verdes urbanas exerce diversas funções como um espaço para a recreação, interpretação e educação ambiental, e assim contribuir para uma maior proximidade entre homem e natureza. O objetivo do estudo é discorrer sobre quais benefícios, incentivos e dificuldades existem para a manutenção e expansão de áreas verdes na cidade e investigar qual a percepção e a relação da população com estes espaços
Keywords: Ecologia; Área verde urbana; Urbanização; Arborização das cidades; Ecologia humana; Qualidade de vida; Limeira (SP)